Progesterone induces a rapid increase in [Ca2+]in of Xenopus laevis oocytes. - Wasserman, W J (1980)
Progesterone causes a rapid increase in the intracellular free calcium level in fully grown amphibian oocytes. When albino Xenopus laevis oocytes were microinjected with the Ca-specific photoprotein aequorin, the calcium-induced luminescence from this protein increased at 40-60 sec after the addition of progesterone and returned to the control level within 5-6 min. No further change in the aequorin glow could be detected through the remainder of the maturation period. This transient increase in cytoplasmic free calcium may be involved in controlling the resumption of oocyte maturation.